Metformin Inhibits Na+/H+ Exchanger NHE3 Resulting in Intestinal Water Loss - Han, Yiran; Yun, C. Chris (Frontiers in Physiology, 2022)
Glycemic control is the key to the management of type 2 diabetes. Metformin is an effective, widely used drug for controlling plasma glucose levels in diabetes, but it is often the culprit of gastrointestinal adverse effects such as abdominal pain, nausea, indigestion, vomiting, and diarrhea. Diarrhea is a complex disease and altered intestinal transport of electrolytes and fluid is a common cause of diarrhea. Na+/H+ exchanger 3 (NHE3, SLC9A3) is the major Na+ absorptive mechanism in the intestine and our previous study has demonstrated that decreased NHE3 contributes to diarrhea associated with type 1 diabetes. The goal of this study is to investigate whether metformin regulates NHE3 and inhibition of NHE3 contributes to metformin-induced diarrhea. We first determined whether metformin alters intestinal water loss, the hallmark of diarrhea, in type 2 diabetic db/db mice. We found that metformin decreased intestinal water absorption mediated by NHE3. Metformin increased fecal water content although mice did not develop watery diarrhea. To determine the mechanism of metformin-mediated regulation of NHE3, we used intestinal epithelial cells. Metformin inhibited NHE3 activity and the effect of metformin on NHE3 was mimicked by a 5’-AMP-activated protein kinase (AMPK) activator and blocked by pharmacological inhibition of AMPK. Metformin increased phosphorylation and ubiquitination of NHE3, resulting in retrieval of NHE3 from the plasma membrane. Previous studies have demonstrated the role of neural precursor cell expressed, developmentally down-regulated 4-2 (Nedd4-2) in regulation of human NHE3. Silencing of Nedd4-2 mitigated NHE3 inhibition and ubiquitination by metformin. Our findings suggest that metformin-induced diarrhea in type 2 diabetes is in part caused by reduced Na+ and water absorption that is associated with NHE3 inhibition, probably by AMPK.